Perspective: Acknowledging Data Work in the Social Media Research Lifecycle - Kinder-Kurlanda, Katharina E.; Weller, Katrin (Frontiers in Big Data, 2020)
This paper provides a novel perspective to the discussion about quality and validity of research based on data collected from social media platforms. We highlight everyday research data management practices and the concrete everyday work required to accomplish social media research along different phases in a data lifecycle. Our perspective is informed by results from a series of qualitative interviews with social media researchers, practical experience of working at a research infrastructure institute, as well as recent literature in the field. We emphasize how social media researchers are entangled in complexities between social media platform providers, social media users, other actors, as well as legal and ethical frameworks, that all affect their everyday research practices. Research design decisions are made iteratively at different stages, involving many decisions that may potentially impact the quality of research. We show that these decisions are often hidden, but that making them visible allows to better understand what drives social media research into specific directions. Consequently, we argue that untangling and documenting choices during the research lifecycle, especially when researchers pursue specific approaches and may have actively decided against others (often due to external factors) is necessary and will help to spot and address structural challenges in the social media research ecosystem that go beyond critiques of individual opportunistic approaches to easily accessible data.